Software Development Hour with Sam Newman. (O'Reilly Media, Inc., 2023)
Join us for a special conversation with Sam Newman and tech leader Pat Kua, where they'll discuss why excellence in software engineering matters more today than ever--and why it's important to continually hone your craft. They'll also explore how engineering practices have evolved and what that implies for the future. This is a chance for you to hear from Sam and Pat about software development, how to use the right tools for your work, and their own career journeys. They'll spend a few minutes covering the trends that are influencing software, then tell you what you need to know to stay ahead of the curve. What you'll learn and how you can apply it Learn what really matters for software design Find out what's coming next for software development This recording of a live event is for you because... You want the chance to hear from Sam Newman and Pat Kua about software development. You want to keep up with the latest developments in engineering practice. Recommended follow-up: Read Building Evolutionary Architectures, second edition (book) Listen to The Manager's Path (audiobook) Read The Staff Engineer's Path (book).